Obesity, dyslipoproteinemia and inflammation - Eckel, Robert (Henry Stewart Talks, 2007)
Normal lipid and lipoprotein physiology, Abnormalities of lipid and lipoprotein physiology in obesity and related mechanisms, Inflammation and obesity, The benefit of weight reduction to favorably modify plasma lipids, lipoproteins and the inflammatory burden in obese patients